Pyrethroids have become a barrier to the daily existence of molluscs (Review) - Raja Saha; Sangita Maiti Dutta (Journal of Hazardous Materials Letters)
Molluscs are significant aquatic organisms, which serve as bioindicator species. They are crucial for maintaining ecological balance as secondary consumers. Molluscs are threatened by pesticides such as pyrethroid insecticides. Pyrethroids are increasingly utilized to control insects in agriculture and gardening. It contaminates aquatic bodies through rainwater runoff and drainage-sewage systems. The current review will focus on the issue of increasing pyrethroid use and its biological effects on molluscs. Due to their highly lipophilic nature, pyrethroids pose a significant risk to these organisms by affecting their metabolites, producing reactive oxygen species, and influencing neurotransmitter actions. The threats to the molluscs and eventually to the concerned aquatic ecosystem warrant significant discussion and attention.